The impact of flanking sequence features on DNA CpG methylation. (June 2021) - Santoni, Daniele
Graphical abstract: Highlights: Flanking sequences of methylated and unmethylated CGs showed different composition and structure complexity. Major differences were observed for GC content and CG dinucleotide frequency in a window size of 300–400 bp. CG self-attraction analysis revealed most different behavior within a window size of 3K bp. The effect of methylated CG on the flanking sequences lasts much more than expected far from the CG reaching Mbp. Abstract: Epigenetics and DNA methylation play a pivotal role in many processes of the cell and we often observe that an aberrant methylation pattern characterizes pathologies. In this work we investigate the role that the flanking sequences of CG s play in the methylation process in human. We built four different CG datasets: methylated, unmethylated, and two randomly extracted ones. We evaluated features associated to the flanking sequences of those CG sets, for different size around the CG, through five measures accounting for different aspects of sequence composition complexity and structure. The analysis performed through those measures revealed evident different behaviors between methylated and unmethylated probe sets. Major differences were observed for GC content and CG dinucleotide frequency in a window size of 300–400 bp and for CG self-attraction in 3K bp. It is remarkable as the effect of methylated CG lasts much more than expected far from the CG .